The Effect of Different Mixing Methods on the pH and Solubility of Mineral Trioxide Aggregate and Calcium-Enriched Mixture - Shahi, Shahriar; Ghasemi, Negin; Rahimi, Saeed; Yavari, Hamid Reza; Samiei, Mohammad; Janani, Maryam; Bahari, Mahmood (Iranian Endodontic Journal, 2015)
Introduction: The aim of this study was to evaluate the effect of different mixing techniques on the pH and solubility of mineral trioxide aggregate (MTA) and calcium-enriched mixture (CEM). Methods and Materials: Five samples were prepared from each biomaterial with different mixing techniques including hand-, amalgamator- or ultrasonic-mixing and were then placed in pre-weighted plastic tubes to determine their pH values. Each tube was then incubated in 10 mL deionized distilled water for 1 h at 37ºC. An electrode was placed in the fluid in each flask at 24ºC and the pH was recorded. In the next stage, six samples from each mixing technique/material were separately placed in glass bottles containing 50 mL of distilled water at 37ºC for 1 h and were let dry for 1 h at 37ºC. The samples’ weights were measured and recorded twice. The procedure was repeated at 1-, 7- and 21-day intervals. Data were analyzed with the repeated measures ANOVA (for solubility) and two-way ANOVA (for pH) and then the post-hoc Tukey’s test was done. Results: The pH of the materials was not significantly affected by mixing methods (P=0.8 for CEM and P=0.1 for MTA). The solubility of all test groups was within the acceptable range (≤3%). However, the solubility of CEM at 1- and 21-day intervals was significantly different (P=0.03 for 1 day and P=0.001 for 21 days). Different mixing techniques had significant effects on the solubility of MTA at the three time points (P=0.004, 0.003 and 0.002 for 1-, 7- and 21-day intervals, respectively). Conclusion: The pH of biomaterials was not influenced by the mixing technique and their solubility was within the acceptable range.